The chemistry of gut microbiome-derived lipopolysaccharides impacts on the occurrence of food allergy in the pediatric age - Di Lorenzo, Flaviana; Paparo, Lorella; Pisapia, Laura; Oglio, Franca; Pither, Molly Dorothy; Cirella, Roberta; Nocerino, Rita; Carucci, Laura; Silipo, Alba; de Filippis, Francesca; Ercolini, Danilo; Molinaro, Antonio; et al. (Frontiers in Molecular Biosciences, 2023)
Introduction: Food allergy (FA) in children is a major health concern. A better definition of the pathogenesis of the disease could facilitate effective preventive and therapeutic measures. Gut microbiome alterations could modulate the occurrence of FA, although the mechanisms involved in this phenomenon are poorly characterized. Gut bacteria release signaling byproducts from their cell wall, such as lipopolysaccharides (LPS), which can act locally and systemically, modulating the immune system function.In the current study gut microbiome-derived LPS isolated from fecal samples of FA and healthy children was chemically characterized providing insights into the carbohydrate and lipid composition as well as into the LPS macromolecular nature. In addition, by means of a chemical/MALDI-TOF MS and MS/MS approach we elucidated the gut microbiome-derived lipid A mass spectral profile directly on fecal samples. Finally, we evaluated the pro-allergic and pro-This is a provisional file, not the final typeset article tolerogenic potential of these fecal LPS and lipid A by harnessing peripheral blood mononuclear cells from healthy donors.Results: By analyzing fecal samples, we have identified different gut microbiome-derived LPS chemical features comparing FA children and healthy controls. We also have provided evidence on a different immunoregulatory action elicited by LPS on peripheral blood mononuclear cells collected from healthy donors suggesting that LPS from healthy individuals could be able to protect against the occurrence of FA, while LPS from children affected by FA could promote the allergic response.Discussion: Altogether these data highlight the relevance of gut microbiome-derived LPS as potential biomarkers for FA and as a target of intervention to limit the disease burden.